Analisis Faktor–Faktor yang Mempengaruhi Investment Opportunity Set dan Implikasinya terhadap Return Saham - Dian Kusumawati; Muhammad Safiq (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2019)
This study aims to examine the capital structure, firm size, sales growth, profitability, liquidity, investment opportunity set and stock returns. This research was conducted on 30 property and real estate companies listed on the Indonesia Stock Exchange in the 2013-2017 observation period with a sample of 150 property and real estate companies. The data collection technique used the documentation method on the official website of the Indonesian Stock Exchange and Yahoo Finance. The data in this study used panel data, and to test the intervention variables with the Structural Equation Model (SEM). The result is that capital structure has no effect on the investment opportunity set; firm size has no effect on the investment opportunity set; sales growth has no effect on the investment opportunity set; profitability has an influence on the investment opportunity set; liquidity has an influence on the investment opportunity set; and the factors that influence the investment opportunity set can increase the effect of the investment opportunity set on stock returns. This is illustrated by the relationship between profitability, investment opportunity set and stock returns which have a significant effect and the relationship between capital structure, investment opportunity set and stock returns which have a significant effect.